Coproducing a new scale with young people aged 10–24 years: a protocol for the development and validation of the Youth Loneliness Scale (YLS) - Lauren Turner; Jennifer Y F Lau; Delia Fuhrmann; Laura Riddleston; Lily Verity; Iqra Alam; Lizet Chavez; Jasmine Conway; Amilah Niaz; Ayla Pollmann; Pamela Qualter; Poppy Spowage; et al. (BMJ Open)
Introduction The high prevalence of loneliness in young people, aged 10–24 years, is increasingly recognised as an urgent global health concern. The experience of loneliness is linked to a wide range of adverse physical and mental health outcomes. A lack of loneliness scales that can accurately capture the authentic experiences of young people has hampered progress in our understanding of the aetiology and sequelae of youth loneliness, as well as the development of preventative policies and interventions. Here, we provide a protocol for developing and validating an age-sensitive loneliness scale for young people aged 10–24 years: the Youth Loneliness Scale (YLS). The scale is designed to measure loneliness in the general population of young people in the UK.Methods and analysis The scale is coproduced with young people from design to dissemination. The scale development process follows a three-phased, multistep approach that includes item development, scale construction and scale evaluation. Item development is achieved via deductive (literature review) and inductive methods (arts workshops and focus groups), as well as a Delphi survey of experts (by profession and experience) for initial refinement. The scale is then constructed via pretesting items in cognitive interviews with young people, and exploratory testing for preliminary evaluation and refinement. Finally, the scale is administered in confirmatory testing, where a full psychometric evaluation is provided.Ethics and dissemination The project was approved by the Queen Mary University of London Research Ethics Committee (Reference: 2024-0231-341) as the lead site and subsequently endorsed by the University of Manchester Research Ethics Committee. The YLS scale and results of its psychometric evaluation will be published open-access. The protocol provided here will allow researchers to evaluate the final scale generated against the plans set out. We also encourage the use and adaptation of the protocol to develop age-sensitive loneliness scales for other populations.